The decline in intergenerational mobility after 1980 - Jonathan Davis; Bhashkar Mazumder (Federal Reserve Bank of Chicago, 2017)
We demonstrate that intergenerational mobility declined sharply for cohorts born between 1942 and 1953 compared to those born between 1957 and 1964. The former entered the labor market prior to the large rise in inequality that occurred around 1980 while the latter cohorts entered the labor market largely afterwards. We show that the rank-rank slope rose from 0.27 to 0.4 and the IGE rose from 0.35 to 0.51. The share of children whose income exceeds that of their parents fell by about 3 percentage points. These findings suggest that relative mobility fell by substantially more than absolute mobility.
Keywords: 330